The Religion of the Educated Classes Revisited: New Religions, the Nonreligious, and Educational Levels - Lewis, James R. (Journal for the scientific study of religion, 2016)
A number of different studies carried out in the late 20th century indicated that new religious movements (NRMs) tended to recruit individuals who were highly educated. In the present study, we confirm this pattern utilizing data from the national censuses of Australia, New Zealand, Canada, England, and Wales. Additionally, we found that educational patterns for NRMs in the censuses tended to fall into at least two subgroups, one of which had educational levels comparable to mainline denominations and the other of which had significantly higher educational achievements. Furthermore, census respondents who expressed some variety of nonbelief were comparable to this latter group in terms of educational accomplishments. We discuss this latter finding in terms of Ernst Troeltsch and Colin Campbell's analysis of secularization.